Contribution to the characterization of emerging photovoltaics technologies in Lima-Peru - Conde Mendoza, Luis Angel (2022)
This Doctoral Thesis contributed to forming a new photovoltaic (PV) laboratory in Lima-Peru, by developing an outdoor characterization system for PV modules. This system enables performance studies of different PV technologies under outdoor conditions. The new laboratory is the first of its kind in Peru due to its appropriate instrumentation for various PV performance research. This system was installed in the outdoor-PV laboratory of the Physics section (12◦2′S, 77◦1′W) at the Pontifical Catholic University of Peru (PUCP) in collaboration with the IDEA research group of the University of Jaén (UJA) in Spain. Seven PV modules of different technologies, and instruments are currently installed to measure environmental conditions. This system measures the current-voltage (I-V) curve of each PV module at five-minute intervals and simultaneously measures module temperature and irradiance. Additionally, the solar spectrum and environmental conditions are measured. With these experimental data, it is possible to carry out characterization and performance studies of PV modules or systems. The system started working in March 2019 and continues to work automatically to date. Three types of PV technologies began to be characterized: Aluminum Back Surface Field (Al- BSF), Hetero-junction with Intrinsic Thin-Layer (HIT), and Amorphous/micro-crystalline silicon tandem (a-Si/μc-Si). Four additional technologies were installed in 2020: Interdigitated Back Contact (IBC), Passivated Emitter Rear Totally Diffused (PERT), Amorphous Silicon (a- Si), and Copper Indium Gallium Selenide (CIGS). The first part describes the characterization system composed of an I-V curve tracer, a multiplexing system, and environmental sensors. PV modules, measuring instruments, sensors, components for circuit boards, and connection diagrams are listed. The automated control section describes the architecture of the software developed in LabVIEW for measurement, visualization, and data storage. In the second part, an analysis of the data extracted from the I-V curves is made, mainly in the maximum power point. For this, a methodology was developed to calibrate the PV modules outdoors. Simple methods such as Osterwald and Constant Fill Factor (FFk) were used to model the maximum power of HIT, Al-BSF, and tandem a-Si/μc-Si, for a year (May 2019 – April 2020). Next, the energy conversion efficiency is analyzed using the Performance Ratio (PR) in the following PV technologies: HIT, Al-BSF, tandem a-Si/μc-Si, IBC, PERT, a-Si, and CIGS for another year (March 2020 – February 2022). In the third part, an experimental study of the solar spectrum was carried out during one year (March 2019 – February 2020). The spectrum was characterized by the Average Photon Energy (APE). It was found that the yearly APE for the study period was 1.923 eV, indicating that the spectrum in Lima has a blue shift with respect to the AM1.5G standard spectrum. Additionally, the variation of the monthly APE during the year is negligible. Then, a theoretical evaluation of the Mismatch Factor (MM) and spectral gain was made for the spectral response (SR) of seven PV technologies: a-Si, Perovskite, CdTe, two CIGS with different SRs, multi-Si, and mono-Si. In the part of conclusions and future works, the objectives achieved and the current state of the research laboratory with the new systems and instruments installed are summarized. Finally, in the appendixes there is more detailed additional information on the circuits, algorithms, and mathematical arrangements that were necessary for the development of the thesis.